Fire buys of central bank collateral assets - Calebe de Roure (Deutsche Bundesbank, 2016)
In times of financial distress, central banks provide unlimited liquidity to avoid fire sales. In response, banks raise their demand for collateral assets, and the short-term scarcity of collateral securities leads to higher prices, the Fire Buy premium. To avoid collateral scarcity, central banks increase the set of eligible collateral assets. However, if the risk-shifting channel is open for these newly eligible securities, banks prefer to pledge them and pay another premium, the Risk-Shifting premium. With the full fixed-income trading book of 26 German banks, I identify each trade of each bank and investigate how unlimited liquidity provision affects collateral prices. Also, I match banks' trades with their balance sheet and show how funding liquidity impacts premia payment. I quantify the Fire Buy premium to be 15.6 bps; and the Risk-Shifting premium on BBB-rated assets to be 65.6 bps.
Keywords: E41; E44; E58; G11; G14; G15; G21; 330; Fire Buy; Risk-Shifting; Haircut Subsidy; ECB; Over-the-Counter Markets